Endoscopic Resection of a Cavernous Hemangioma in the Sigmoid Colon: A Case Report - Noora Al-Khater; Mohamed Mohamed; Afra Juma; Faisal Abubaker; Sameer Ansari (Gastro Hep Advances, 2024)
Hemangiomas in the gastrointestinal tract are extremely rare, benign vascular tumors, known for their associated complication of bleeding. They are usually difficult to diagnose, despite the characteristic definition of radiolucent phleboliths on radiology and purplish, tannish brown nodule or polyp on endoscopy. Surgical resection is the treatment of choice. We describe a rare case of sigmoid colon cavernous hemangioma in a 49-year-old male who underwent colonoscopy for lower abdominal pain and revealed a large pedunculated polyp in the sigmoid colon measuring 1.7 cm in diameter. The hemangioma was completely resected endoscopically via hot snare with a favorable outcome.